Genetic Approach on Descriptive Modeling of Data Mining (International Journal of Engineering and Computer Science, 2017)
The fast developing computer science and engineering techniques has made the information easy to capture process and store in databases. Information or data are considered as elementary variable facts. Knowledge is considered as a set of instructions, which describes how these facts can be interpreted and use[1]. Data describes the actual state of the world; however knowledge describes the structure of the world and consists of principal and laws. How to gather, store and retrieve data is considered in database. Soft computing (SC) is an evolving collection of methodologies, which aims to exploit tolerance for imprecision, uncertainty, and partial truth to achieve robustness, tractability, and low cost. SC provides an attractive opportunity to represent the ambiguity in human thinking with real life uncertainty. Soft computing has recently been playing an important role in advanced knowledge processing. An advanced learning method using a combination of perception and motion has been introduced. Emergent, self-organizing, reflective, and interactive (among human beings, environment, and artificial intelligence) knowledge processing is considered by using soft computing and by borrowing ideas from bio-information processing [2].